creativity in time of crisis (Revista Electrónica REDINE, 2018)
Creativity has always been present in humans, is the property that sets us apart from the rest of the species, and is the power which has allowed us to survive across the history. However, in this times, which live our higher education system when we take the following question. How can people resolves an issue from the point of view of thinking and creative behavior? Is there when we review, we read, we researched, indagated and speculated about the table of salvation that may indicate the way for the teacher and the student to overload conditions.
Keywords: creativity; overload; university